Contextual Eco-Pedagogy through Arts Education in Early Childhood: A Case Study of the Lima Gunung Community - Arbi, Bahtiar; Jazuli, Muhammad; Wadiyo; Cahyono, Agus; Trinanda Kusuma Adi, Brian (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Early childhood art education is often framed through skill acquisition, classroom activity, or measurable creative outcomes, while its role in ecological and spiritual meaning-making remains less visible. This study examines the Lima Gunung Community in Magelang, Central Java, where children encounter art through communal rehearsals, ritual processions, gamelan sessions, symbolic objects, agricultural landscapes, and intergenerational guidance. Using a qualitative ethnographic case study design, the research was conducted across four embedded art studios through prolonged field engagement between 2022 and 2025. Data were generated through participant observation, semi-structured interviews with adult key informants, informal child conversations, and documentation of artistic, ritual, and visual materials. Interpretive thematic analysis was used to examine children’s forms of participation, ecological and spiritual meaning-making, and recurring pedagogical patterns across sites. The findings show that children’s arts learning developed through graduated participation rather than formal instruction. Children watched, imitated, carried symbolic objects, joined simple performances, listened to stories, began activities with prayer, and re-enacted ritual fragments in play. These acts did not demonstrate fixed ecological literacy or complete spiritual formation; they indicated emerging meaning-making shaped by community mediation, environmental immersion, symbolic participation, and spiritual orientation. The study contributes to early childhood ecopedagogy by showing that ecological and spiritual learning may be lived through community-based artistic practice, local ritual, and everyday relations with land and water, rather than only designed as school-based environmental curriculum. It also positions local cultural communities as sources of pedagogical knowledge for rethinking arts-based, place-based, and spiritually attentive early childhood education within Global South contexts without reducing local practice to universal transferable instructional technique.